Membrane electrode catalyst layer and preparation method thereof, membrane electrode and fuel cell

By filling the holes of the membrane electrode catalytic layer with thermal conductivity materials to form an orderly thermal conductivity channel, the problem of insufficient thermal conductivity of the traditional membrane electrode catalytic layer is solved, and higher thermal conductivity and power density are achieved.

CN119674099APending Publication Date: 2025-03-21FAW JIEFANG AUTOMOTIVE CO
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411760305.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-03
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The thermal conductivity of the traditional membrane electrode catalytic layer is insufficient, resulting in the inability to transmit heat outward in time, affecting the temperature control of the membrane electrode and the proton conduction ability of the proton membrane.

Method used

A catalytic layer containing a pore structure is designed to form an ordered thermal conduction channel by filling the pores of the catalytic material layer with a specific content of thermally conductive material, such as nanoboronitride.

Benefits of technology

The thermal conductivity of the membrane electrode catalytic layer is significantly improved, and the heat generated by the reaction can be transmitted outward in a timely manner, thereby improving the power density and temperature regulation efficiency of the membrane electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674099A_ABST
    Figure CN119674099A_ABST
Patent Text Reader

Abstract

The invention provides a membrane electrode catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell. The membrane electrode catalytic layer comprises a catalytic material layer and a heat conduction material, holes are formed in the catalytic material layer, at least part of the heat conduction material is filled in the holes, the material of the catalytic material layer comprises a catalyst, and the mass ratio of the catalyst to the heat conduction material is 1: (0.02-0.05). The catalyst layer comprises the porous structure, the porous structure is filled with the heat conduction material with the specific content, and the holes filled with the heat conduction material form ordered heat conduction channels in the catalyst layer, so that the heat conductivity of the membrane electrode catalyst layer can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of fuel cell technology, and in particular to a membrane electrode catalyst layer and a preparation method thereof, a membrane electrode and a fuel cell. Background Art

[0002] The membrane electrode is the core of the proton exchange membrane fuel cell and is the place where electricity is generated. The membrane electrode is mainly composed of a proton membrane, a cathode catalyst layer, an anode catalyst layer, a cathode gas diffusion layer and an anode gas diffusion layer; among them, the proton membrane transports the protons generated by the anode catalytic reaction to the cathode and combines with the oxygen ions generated by the cathode catalytic reaction to generate water. The transmission of protons by the proton membrane decreases significantly with the increase of temperature, and the catalyst layer next to the proton membrane is where chemical reactions occur and a large amount of heat is generated. The large amount of heat generated by the chemical reaction is mainly transported outward through heat conduction of the catalyst layer, gas diffusion layer and electrode plate, and output to the fuel cell through the coolant, thereby realizing the regulation of the membrane electrode temperature.

[0003] With the development of fuel cells, fuel cells are moving towards high power density, high current density, and high operating temperature. The heat generated by the fuel cell membrane electrode at the rated point increases, and the traditional membrane electrode cannot meet the heat dissipation requirements of the fuel cell.

[0004] At present, the inter-surface thermal conductivity of the catalyst layer in the membrane electrode of proton exchange membrane fuel cells is generally less than 1W / mK. The heat cannot be transmitted outward in time, which is not conducive to the temperature control of the membrane electrode, thereby reducing the proton conduction capacity of the proton membrane and affecting the performance of the membrane electrode. Summary of the invention

[0005] Based on this, one or more embodiments of the present application provide a catalytic layer with excellent thermal conductivity and a preparation method thereof, and correspondingly provide a membrane electrode and a fuel cell including the catalytic layer, wherein the fuel cell has a high power density and voltage.

[0006] According to the first aspect of the present application, a membrane electrode catalyst layer is provided, comprising a catalytic material layer and a thermally conductive material, wherein the catalytic material layer has holes, and at least part of the thermally conductive material is filled in the holes; the material of the catalytic material layer comprises a catalyst, and the mass ratio of the catalyst to the thermally conductive material is 1:(0.02~0.05).

[0007] In one embodiment, the thermal conductive material includes one or more of nano boron nitride, silicon carbide and aluminum nitride.

[0008] In one embodiment, the particle size of the thermal conductive material is 100nm~500nm.

[0009] In one embodiment, the catalyst includes one or more of a Pt / C catalyst and a Pt alloy catalyst.

[0010] In one of the embodiments, the material of the catalytic material layer also includes an ionic polymer, and the mass ratio of the catalyst to the ionic polymer is 1:(6-8).

[0011] In one embodiment, the membrane electrode catalyst layer satisfies at least one of the following characteristics:

[0012] (1) The porosity of the catalytic material layer is 40% to 70%;

[0013] (2) The average pore size of the pores is 300 nm to 2000 nm.

[0014] According to the second aspect of the present application, a method for preparing a membrane electrode catalyst layer is provided, comprising the following steps:

[0015] preparing a catalytic material layer having holes, and filling the holes with a thermal conductive material;

[0016] Wherein, the material of the catalytic material layer includes a catalyst, and the mass ratio of the catalyst to the thermal conductive material is 1: (0.02-0.05).

[0017] In one embodiment, preparing a catalytic material layer having holes comprises the following steps:

[0018] Mixing a catalyst, an ionic polymer, a pore former and a dispersant to obtain a first slurry;

[0019] The first slurry is coated on a substrate, and subjected to a first drying treatment and a heat treatment to obtain the catalytic material layer having holes.

[0020] In one embodiment, filling the hole with a thermally conductive material comprises the following steps:

[0021] A second slurry containing a thermally conductive material is applied to the surface of the catalytic material layer, so that at least a portion of the second slurry penetrates into the holes, and a second drying process is performed.

[0022] In one embodiment, the pore former includes one or more of ammonium bicarbonate and ammonium oxalate.

[0023] In one embodiment, the mass ratio of the catalyst to the pore-forming agent is 1:(0.04-0.08).

[0024] In one embodiment, the preparation method satisfies at least one of the following characteristics:

[0025] (1) The dispersant is selected from one or more of water, n-propanol and isopropanol;

[0026] (2) The temperature of the first drying treatment is 40°C to 80°C and the time is more than 5 minutes;

[0027] (3) The heat treatment temperature is 60°C to 100°C and the time is more than 30 minutes;

[0028] (4) The temperature of the second drying treatment is 40°C to 80°C and the time is more than 5 minutes.

[0029] According to the third aspect of the present application, a membrane electrode is provided, comprising a proton membrane, a cathode catalyst layer and an anode catalyst layer, wherein the cathode catalyst layer and the anode catalyst layer are respectively arranged on opposite sides of the proton membrane, and the cathode catalyst layer and / or the anode catalyst layer are selected from the above-mentioned membrane electrode catalyst layer or the membrane electrode catalyst layer prepared by the above-mentioned preparation method.

[0030] In one embodiment, the platinum loading in the anode catalyst layer is 0.05 mg / cm 2 ~0.1mg / cm 2 The platinum loading in the cathode catalyst layer is 0.2 mg / cm 2 ~0.4mg / cm 2 .

[0031] In one embodiment, the membrane electrode further includes an anode gas diffusion layer and a cathode gas diffusion layer;

[0032] The anode gas diffusion layer is arranged on a side of the anode catalyst layer away from the proton membrane, and the cathode gas diffusion layer is arranged on a side of the cathode catalyst layer away from the proton membrane.

[0033] According to a fourth aspect of the present application, a fuel cell is provided, comprising the above-mentioned membrane electrode.

[0034] Compared with the traditional technology, this application has the following beneficial effects:

[0035] The catalyst layer of the present application includes a pore structure, and the porous structure is filled with a specific content of a thermally conductive material. The pores filled with the thermally conductive material form an ordered thermally conductive channel in the catalyst layer, thereby improving the thermal conductivity of the membrane electrode catalyst layer.

[0036] In addition, the membrane electrode including the catalytic layer of the present application can transfer the heat generated by the reaction to the outside in a timely manner, thereby improving the power density of the membrane electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0037] In order to more clearly illustrate the specific implementation methods of the present application or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative work.

[0038] Figure 1 This is a polarization curve diagram of the membrane electrode prepared in Example 1 of the present application;

[0039] Figure 2 This is a polarization curve diagram of the membrane electrode prepared in Example 5 of the present application;

[0040] Figure 3 This is a polarization curve diagram of the membrane electrode prepared in Comparative Example 1 of the present application;

[0041] Figure 4 This is the polarization curve diagram of the membrane electrode prepared in Comparative Example 2 of the present application. DETAILED DESCRIPTION

[0042] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application, so the present application is not limited by the specific embodiments disclosed below.

[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present application. The terms used herein in the specification of the present application are only for the purpose of describing specific embodiments and are not intended to limit the present application. Unless otherwise specifically stated, various raw materials, reagents, instruments and equipment used in the present application, etc. can be purchased from the market or can be prepared by existing methods.

[0044] In the present application, "plurality", "multiple", "multiple times", "multiples", etc., unless otherwise specified, refer to a number greater than 2 or equal to 2. For example, "one or more" means one or greater than or equal to two.

[0045] In this application, "optionally", "optional", and "optional" mean optional or dispensable, that is, any one of the two parallel schemes of "yes" or "no". If multiple "options" appear in a technical solution, unless otherwise specified and there is no contradiction or mutual restriction, each "optional" is independent.

[0046] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0047] In the present application, when it comes to numerical intervals (i.e., numerical ranges), unless otherwise specified, the optional numerical distribution is considered continuous within the above numerical interval, and includes the two numerical endpoints (i.e., the minimum and maximum values) of the numerical range, and each numerical value between the two numerical endpoints. Unless otherwise specified, when the numerical interval only refers to the integers within the numerical interval, it includes the two endpoint integers of the numerical range, and each integer between the two endpoints. In this article, it is equivalent to directly listing each integer, such as t is an integer selected from 1-10, indicating that t is any integer selected from the integer group consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9 and 10. In addition, when multiple ranges are provided to describe features or characteristics, these ranges can be combined. In other words, unless otherwise specified, the ranges disclosed herein should be understood to include any and all sub-ranges included therein.

[0048] The temperature parameters in this application, unless otherwise specified, are allowed to be either constant temperature treatment or to vary within a certain temperature range. It should be understood that the constant temperature treatment allows the temperature to fluctuate within the accuracy range controlled by the instrument. Fluctuations within the range of ±5°C, ±4°C, ±3°C, ±2°C, and ±1°C are allowed.

[0049] Some embodiments of the present application provide a membrane electrode catalyst layer, including a catalytic material layer and a thermally conductive material, the catalytic material layer having pores, and at least a portion of the thermally conductive material is filled in the pores; the material of the catalytic material layer includes a catalyst, and the mass ratio of the catalyst to the thermally conductive material is 1: (0.02~0.05).

[0050] The catalytic layer of the present application contains a pore structure, which can vertically penetrate the catalytic layer and communicate with the proton membrane; adding a specific mass ratio of thermal conductive material and loading it in the pore structure can form a uniformly distributed and ordered thermal conductive channel, thereby improving the thermal conductivity of the catalytic layer under high current density conditions; when the amount of thermal conductive material added exceeds the above-mentioned range of the present application, it may cover the catalytic active sites, masking the high thermal conductivity effect, and the effect of improving the overall thermal conductivity is not obvious.

[0051] As an example, the mass ratio of the catalyst to the thermally conductive material can be 1:0.02, 1:0.022, 1:0.024, 1:0.026, 1:0.028, 1:0.03, 1:0.032, 1:0.034, 1:0.036, 1:0.038, 1:0.04, 1:0.042, 1:0.044, 1:0.046, 1:0.048, 1:0.05 or any value within the range formed by any two of the above values.

[0052] In some embodiments, the thermally conductive material is completely filled in the hole.

[0053] In some specific embodiments, the mass ratio of the catalyst to the thermally conductive material is 1:(0.04-0.05). It is understandable that controlling the mass ratio of the catalyst to the thermally conductive material within the above range can further improve the thermal conductivity of the catalyst layer.

[0054] In some embodiments, the thermal conductive material includes one or more of nano boron nitride, silicon carbide and aluminum nitride. The thermal conductive material has good thermal conductivity, and is coated in the porous structure that vertically penetrates the catalyst layer to form an ordered high thermal conductivity channel, which is beneficial to discharge the heat released by the catalyst layer reaction out of the membrane electrode.

[0055] In some optional examples, the thermally conductive material is selected from nano boron nitride.

[0056] In some embodiments, the particle size of nano-boron nitride is 100 nm to 500 nm. It is understandable that when the particle size of nano-boron nitride is controlled within the above range, it can enter the pores to effectively fill them without blocking the pores.

[0057] As an example, the particle size of nano-boron nitride can be 100nm, 110nm, 120nm, 130nm, 140nm, 150nm, 160nm, 170nm, 180nm, 190nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm or any value within the range formed by any two of the above values.

[0058] In some embodiments, the catalyst includes one or more of a Pt / C catalyst and a Pt alloy catalyst. The above catalyst can be used to catalyze hydrogen oxidation reaction at the anode and oxygen reduction reaction at the cathode to achieve efficient electrochemical energy conversion.

[0059] In some of the embodiments, the material of the catalytic material layer also includes an ionic polymer, and the mass ratio of the catalyst to the ionic polymer is 1:(6-8).

[0060] As an example, the mass ratio of catalyst to ionomer can be 1:6, 1:6.1, 1:6.2, 1:6.3, 1:6.4, 1:6.5, 1:6.6, 1:6.7, 1:6.8, 1:6.9, 1:7, 1:7.1, 1:7.2, 1:7.3, 1:7.4, 1:7.5, 1:7.6, 1:7.7, 1:7.8, 1:7.9, 1:8 or any value within the range formed by any two of the above values.

[0061] In some specific examples, the ionic polymer includes a perfluorosulfonic acid polymer; alternatively, the ionic polymer includes Nafion.

[0062] In some embodiments, the porosity of the catalytic layer is 40% to 70%.

[0063] As an example, the porosity of the catalytic layer can be 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54%, 55%, 56%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64%, 65%, 66%, 67%, 68%, 69%, 70% or any value within the range formed by any two of the above values.

[0064] In some embodiments, the average pore size of the porous structure is 300 nm to 2000 nm.

[0065] The above-mentioned catalyst layer of the present application has high thermal conductivity, which is beneficial to discharge the heat generated by the reaction of the catalyst layer out of the membrane electrode and can strengthen the thermal management of the membrane electrode.

[0066] Some embodiments of the present application also provide a method for preparing a catalytic layer, including S100.

[0067] S100: preparing a catalytic material layer having holes, and filling the holes with a thermal conductive material.

[0068] In some embodiments, the material of the catalytic material layer in S100 includes a catalyst, and the mass ratio of the catalyst to the thermal conductive material is 1: (0.004-0.04).

[0069] As an example, the mass ratio of the catalyst to the thermally conductive material can be 1:0.004, 1:0.005, 1:0.006, 1:0.007, 1:0.008, 1:0.009, 1:0.01, 1:0.012, 1:0.014, 1:0.016, 1:0.018, 1:0.02, 1:0.022, 1:0.024, 1:0.026, 1:0.028, 1:0.03, 1:0.032, 1:0.034, 1:0.036, 1:0.038, 1:0.04 or any value within the range formed by any two of the above values.

[0070] In some embodiments, preparing a catalytic material layer having holes includes S110 to S120.

[0071] S110: Mixing a catalyst, an ionic polymer, a pore-forming agent and a dispersing solvent to obtain a first slurry.

[0072] S120: coating the first slurry on the substrate, and performing a first drying treatment and a heat treatment to obtain a catalytic material layer having holes.

[0073] In some embodiments, the step of filling the hole with a thermally conductive material includes S130.

[0074] S130: coating a second slurry containing a thermally conductive material onto the surface of the catalytic material layer, allowing at least a portion of the second slurry to penetrate into the pores, and performing a second drying process.

[0075] In some embodiments, the pore former in S110 includes one or more of ammonium bicarbonate and ammonium oxalate.

[0076] In some optional examples, the pore-forming agent is selected from ammonium bicarbonate. Ammonium bicarbonate can begin to decompose at about 30°C, while ammonium oxalate requires a temperature of about 95°C to begin to decompose; in comparison, the use of ammonium bicarbonate can simplify the preparation process and save production costs.

[0077] Understandably, ammonium bicarbonate will decompose under heating conditions to produce three gaseous products: ammonia, water vapor and carbon dioxide, thereby forming a porous structure in the catalyst layer.

[0078] In some embodiments, the mass ratio of the catalyst to the pore former is 1:(0.04-0.08).

[0079] It can be understood that controlling the mass ratio of the catalyst to the pore-forming agent within the above range can make the porosity of the prepared catalytic material layer moderate and ultimately form a plurality of evenly distributed heat-conducting channels.

[0080] As an example, the mass ratio of the catalyst to the pore former may be 1:0.04, 1:0.05, 1:0.06, 1:0.07, 1:0.08, or any value within the range formed by any two of the above values.

[0081] In some embodiments, the dispersing solvent is selected from one or more of water, n-propanol and isopropanol.

[0082] In some optional embodiments, the dispersing solvent is selected from water and isopropanol. Optionally, the mass ratio of water to isopropanol is 1:4.

[0083] In some embodiments, the catalyst, ionic polymer, pore former and dispersion solvent are mixed by ultrasonic dispersion in S110. Optionally, the temperature of ultrasonic dispersion is below 10°C, and the time of ultrasonic dispersion is 0.5h to 3h.

[0084] In some embodiments, the temperature of the first drying process in S120 is 40° C. to 80° C., and the time is more than 5 minutes.

[0085] In some optional embodiments, the first drying process lasts for 5 minutes to 30 minutes.

[0086] Understandably, if the drying time is too long, the pore former may decompose prematurely, resulting in the accumulation of solid matter and the collapse of the pores.

[0087] As an example, the temperature of the first drying treatment can be 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any value within the range formed by any two of the above values.

[0088] In some embodiments, the heat treatment in S120 is performed at a temperature of 60° C. to 100° C. for a time of more than 30 minutes.

[0089] In some optional embodiments, the heat treatment time is 30 min to 60 min.

[0090] Understandably, if the heat treatment time is too long, the catalyst will undergo ripening and aggregation, thereby affecting the performance of the membrane electrode.

[0091] As an example, the temperature of the heat treatment can be but is not limited to 60°C, 61°C, 62°C, 63°C, 64°C, 65°C, 66°C, 67°C, 68°C, 69°C, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, 92°C, 94°C, 96°C, 98°C, 100°C or any value within the range formed by any two of the above values.

[0092] It is understood that the heat treatment is performed to remove the residual pore former in the catalyst layer.

[0093] In some embodiments, the substrate in S120 is a proton membrane.

[0094] In some optional embodiments, the first slurry is coated on both sides of the proton membrane to obtain a cathode catalyst material layer and an anode catalyst material layer respectively.

[0095] In some embodiments, the temperature of the second drying process in S130 is 40° C. to 80° C., and the time is more than 5 minutes.

[0096] In some optional embodiments, the second drying time is 5 min to 30 min.

[0097] As an example, the temperature of the second drying may be, but is not limited to, 40°C, 41°C, 42°C, 43°C, 44°C, 45°C, 46°C, 47°C, 48°C, 49°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C or any value within the range formed by any two of the above values.

[0098] The preparation method of the present application adds a pore-forming agent to the slurry for preparing the catalyst layer, and performs heat treatment after coating the first slurry to remove the pore-forming agent, thereby forming a plurality of relatively uniformly distributed pore structures connected to the proton membrane in the catalyst layer; then, a second slurry containing a thermally conductive material is prepared and coated on the surface of the catalyst material layer so that the second slurry penetrates into the pores to form a high thermal conductivity channel.

[0099] Some embodiments of the present application also provide a membrane electrode, which includes a proton membrane, a cathode catalyst layer and an anode catalyst layer, wherein the cathode catalyst layer and the anode catalyst layer are respectively arranged on two opposite sides of the proton membrane, and the cathode catalyst layer and / or the anode catalyst layer are selected from the above-mentioned membrane electrode catalyst layer or the membrane electrode catalyst layer prepared by the above-mentioned preparation method.

[0100] In some optional embodiments, the proton membrane is selected from commercial proton membranes with product models Nafion112 or Nafion119.

[0101] In some embodiments, the platinum loading in the anode catalyst layer is 0.05 mg / cm 2 ~0.1mg / cm 2 The platinum loading in the cathode catalyst layer is 0.2 mg / cm 2 ~0.4mg / cm 2 .

[0102] In some embodiments, the membrane electrode further includes an anode gas diffusion layer and a cathode gas diffusion layer; the anode gas diffusion layer is arranged on the side of the anode catalyst layer away from the proton membrane, and the cathode gas diffusion layer is arranged on the side of the cathode catalyst layer away from the proton membrane.

[0103] In some optional embodiments, the anode gas diffusion layer and the cathode gas diffusion layer are each independently selected from commercial gas diffusion layers manufactured by Toray, SGL or JNTG.

[0104] In some embodiments, the membrane electrode further comprises a sealing layer, and the sealing layer is used to seal and bond the anode catalyst layer, the proton membrane and the cathode catalyst layer.

[0105] The membrane electrode including the above-mentioned catalytic layer has a high temperature control efficiency, and the proton membrane in the membrane electrode will not reduce the proton conductivity due to excessively high temperature.

[0106] Some embodiments of the present application also provide a fuel cell, comprising the above-mentioned membrane electrode.

[0107] In some embodiments, the fuel cell is a proton exchange membrane fuel cell.

[0108] The fuel cell prepared by using the above membrane electrode has good heat dissipation performance, can reduce the requirements for coolant circulation and the power consumption of the fuel cell generator, and thus can output more electrical energy.

[0109] The present application will be further described below in conjunction with specific examples and comparative examples, but they should not be construed as limiting the scope of protection of the present application. The raw materials involved in the following specific examples, unless otherwise specified, can all be sourced from commercial sources, the instruments used, unless otherwise specified, can all be sourced from commercial sources, and the processes involved, unless otherwise specified, are all conventionally selected by those skilled in the art.

[0110] The models of some materials and reagents used in the examples and comparative examples of the present application are as follows: the brand of the gas diffusion layer is JNTG; the catalyst is a Pt / C catalyst with the product model JM9100 (Pt content is 60wt%); the brand of Nafion ionomer is Dupont; the brand of proton membrane is Nafion112 proton membrane; other chemical reagents such as isopropanol are from Sinopharm Chemical Reagent Co., Ltd. and Aladdin Chemical Reagent Co., Ltd.

[0111] Example 1

[0112] 1) Weigh 0.50 g of commercial Pt / C catalyst (Pt content is 60 wt%), add 14.00 g of water, 56.00 g of isopropanol, 0.04 g of ammonium bicarbonate and 3.50 g of 20 wt% Nafion solution; perform ultrasonic treatment at below 10° C. for 2 hours to obtain a uniformly dispersed first slurry; wherein the mass ratio of the catalyst to the pore-forming agent is 1:0.08.

[0113] 2) The first slurry prepared in 1) is ultrasonically sprayed on both sides of the proton membrane to form a cathode catalyst layer wet membrane and an anode catalyst layer wet membrane respectively.

[0114] 3) Drying the cathode catalyst layer wet membrane and the anode catalyst layer wet membrane obtained in 2) at 60° C. for 10 min to obtain a cathode catalyst layer dry membrane and an anode catalyst layer dry membrane.

[0115] 4) The cathode catalyst layer dry film and the anode catalyst layer dry film prepared in 3) are heat-treated at 80° C. for 1 h to obtain a cathode catalyst material layer and an anode catalyst material layer having a porous structure.

[0116] 5) Weigh 0.02 g of nano boron nitride with a particle size of 200 nm, add 1.2 g of water and 4.8 g of isopropanol, and ultrasonicate at below 10° C. for 2 hours to obtain a uniformly dispersed second slurry; wherein the mass ratio of the catalyst to the boron nitride is 1:0.04.

[0117] 6) The slurry obtained in 5) is ultrasonically sprayed on the surface of the cathode catalyst layer intermediate and the anode catalyst layer intermediate, and dried at 60°C for 10 minutes to form a high thermal conductivity ordered channel that vertically penetrates the catalyst layer to obtain the cathode catalyst layer and the anode catalyst layer. The platinum loading in the cathode catalyst layer is 0.4 mg / cm 2 The platinum loading in the anode catalyst layer is 0.1 mg / cm 2 The porosity of the cathode catalyst layer is 50%, and the average pore size of the porous structure is 300 nm; the porosity of the anode catalyst layer is 50%, and the average pore size of the porous structure is 300 nm.

[0118] 7) The cathode catalyst layer, proton membrane and anode catalyst layer are sealed and bonded using a PEN frame, and the JNTG gas diffusion layer is hot-pressed to form a membrane electrode.

[0119] 8) The performance of the membrane electrode was tested with reference to GB / T 20042.5-2009. The results are shown in Table 1; Figure 1 This is the polarization curve of the membrane electrode prepared in Example 1.

[0120] Example 2

[0121] The method is basically the same as Example 1, except that the mass ratio of the catalyst to the nano-boron nitride in step 5) is different; specifically, the mass ratio of the catalyst to the nano-boron nitride is 1:0.05.

[0122] Example 3

[0123] It is basically the same as Example 1, except that the mass ratio of the catalyst to the pore-forming agent in step 1) is different; specifically, the mass ratio of the catalyst to the pore-forming agent is 1:0.04.

[0124] Example 4

[0125] The method is basically the same as Example 1, except that the pore-forming agent is replaced by ammonium bicarbonate of equal mass.

[0126] Example 5

[0127] It is basically the same as Example 1, except that the mass ratio of the catalyst to boron nitride in step 5) is different; specifically, the mass ratio of the catalyst to boron nitride is 1:0.02.

[0128] Figure 2 This is the polarization curve of the membrane electrode prepared in Example 5.

[0129] Comparative Example 1

[0130] It is basically the same as Example 1, except that the mass ratio of the catalyst to boron nitride in step 5) is different; specifically, the mass ratio of the catalyst to boron nitride is 1:0.08.

[0131] Figure 3 This is the polarization curve of the membrane electrode prepared in Comparative Example 1.

[0132] Comparative Example 2

[0133] It is basically the same as Example 1, except that it does not include the steps of preparing the second slurry and spraying the second slurry on the surface of the catalyst layer intermediate, that is, the porous structures of the cathode catalyst layer and the anode catalyst layer prepared in this comparative example do not load nano boron nitride.

[0134] Figure 4 This is the polarization curve of the membrane electrode prepared in Comparative Example 2.

[0135] Comparative Example 3

[0136] It is basically the same as Example 1, except that the raw materials for preparing the first slurry do not contain ammonium bicarbonate, that is, the cathode catalyst layer and the anode catalyst layer prepared in this comparative example do not contain a porous structure, and the boron nitride particles are randomly dispersed in the catalyst layer.

[0137] The performance of the membrane electrodes prepared in Examples 1 to 5 and Comparative Examples 1 to 2 are shown in Table 1.

[0138] Table 1

[0139]

[0140] The membrane electrode prepared in the embodiment of the present application has a current density of 2.9A / cm 2 When the power density is ≥1.22W / cm 2 , voltage ≥ 0.421V; and has good thermal conductivity.

[0141] In Example 5, the addition ratio of nano-boron nitride is reduced, and the power density and voltage of the membrane electrode finally obtained are improved, but lower than the membrane electrode obtained in Example 1.

[0142] The amount of nano-boron nitride added in Comparative Example 1 is too high, and the power density of the membrane electrode finally obtained is basically the same as that of Comparative Example 2 without adding nano-boron nitride; it can be seen that although the excessively high thermal conductive material helps to discharge heat at high current density points and is beneficial to temperature control, it occupies a larger space in the catalytic layer and covers more active sites, which is not conducive to the overall performance of the membrane electrode.

[0143] In Comparative Example 2, nano boron nitride was not added, and the power density of the membrane electrode finally obtained was significantly reduced; it can be seen that the addition of highly thermally conductive nano boron nitride helps the performance of the fuel cell membrane electrode under high current density (i.e., high hot spots), making temperature control in the membrane electrode easier and the proton membrane will not reduce proton conduction due to excessively high temperature.

[0144] In Comparative Example 3, no pore-forming material was added, only high thermal conductivity material was added, and the final membrane electrode power density was low; it can be seen that in the construction of the pore structure of the catalytic layer without a pore-forming agent, the role of the thermal conductor is relatively limited.

[0145] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0146] The above-mentioned embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the present application shall be subject to the attached claims.

Claims

1. A membrane electrode catalyst layer, characterized in that: It includes a catalytic material layer and a thermal conductive material, wherein the catalytic material layer has holes, and at least part of the thermal conductive material is filled in the holes; the material of the catalytic material layer includes a catalyst, and the mass ratio of the catalyst to the thermal conductive material is 1: (0.02-0.05).

2. The membrane electrode catalyst layer according to claim 1, characterized in that: The thermal conductive material includes one or more of nano boron nitride, silicon carbide and aluminum nitride.

3. The membrane electrode catalyst layer according to claim 1 or 2, characterized in that: The particle size of the thermal conductive material is 100nm~500nm.

4. The membrane electrode catalyst layer according to claim 1 or 2, characterized in that: The catalyst includes one or more of a Pt / C catalyst and a Pt alloy catalyst.

5. The membrane electrode catalyst layer according to claim 1 or 2, characterized in that: The material of the catalytic material layer also includes an ionic polymer, and the mass ratio of the catalyst to the ionic polymer is 1:(6-8).

6. The membrane electrode catalyst layer according to claim 1 or 2, characterized in that: The membrane electrode catalyst layer satisfies at least one of the following characteristics: (1) The porosity of the catalytic material layer is 40% to 70%; (2) The average pore size of the pores is 300 nm to 2000 nm.

7. A method for preparing a membrane electrode catalyst layer, characterized in that: The steps include: preparing a catalytic material layer having holes, and filling the holes with a thermal conductive material; Wherein, the material of the catalytic material layer includes a catalyst, and the mass ratio of the catalyst to the thermal conductive material is 1: (0.02-0.05).

8. The method for preparing a membrane electrode catalyst layer according to claim 7, characterized in that: The preparation of the catalytic material layer having holes comprises the following steps: Mixing a catalyst, an ionic polymer, a pore former and a dispersant to obtain a first slurry; The first slurry is coated on a substrate, and subjected to a first drying treatment and a heat treatment to obtain the catalytic material layer having holes.

9. The method for preparing a membrane electrode catalyst layer according to claim 8, characterized in that: Filling the hole with thermally conductive material comprises the following steps: A second slurry containing a thermally conductive material is applied to the surface of the catalytic material layer, so that at least a portion of the second slurry penetrates into the holes, and a second drying process is performed.

10. The method for preparing a membrane electrode catalyst layer according to claim 8 or 9, characterized in that: The pore former includes one or more of ammonium bicarbonate and ammonium oxalate.

11. The method for preparing a membrane electrode catalyst layer according to claim 8 or 9, characterized in that: The mass ratio of the catalyst to the pore-forming agent is 1:(0.04-0.08).

12. The method for preparing a membrane electrode catalyst layer according to claim 9, characterized in that: The preparation method meets at least one of the following characteristics: (1) The dispersant is selected from one or more of water, n-propanol and isopropanol; (2) The temperature of the first drying treatment is 40°C to 80°C and the time is more than 5 minutes; (3) The heat treatment temperature is 60°C to 100°C and the time is more than 30 minutes; (4) The temperature of the second drying treatment is 40°C to 80°C and the time is more than 5 minutes.

13. A membrane electrode, characterized in that: It comprises a proton membrane, a cathode catalyst layer and an anode catalyst layer, wherein the cathode catalyst layer and the anode catalyst layer are respectively arranged on opposite sides of the proton membrane, and the cathode catalyst layer and / or the anode catalyst layer are selected from the membrane electrode catalyst layer described in claims 1 to 6 or the membrane electrode catalyst layer prepared by the preparation method described in any one of claims 7 to 12.

14. The membrane electrode according to claim 13, characterized in that: The platinum loading in the anode catalyst layer is 0.05 mg / cm 2 ~0.1mg / cm 2 The platinum loading in the cathode catalyst layer is 0.2 mg / cm 2 ~0.4mg / cm 2 .

15. The membrane electrode according to claim 13 or 14, characterized in that: The membrane electrode also includes an anode gas diffusion layer and a cathode gas diffusion layer; The anode gas diffusion layer is arranged on a side of the anode catalyst layer away from the proton membrane, and the cathode gas diffusion layer is arranged on a side of the cathode catalyst layer away from the proton membrane.

16. A fuel cell, characterized in that: A membrane electrode comprising the membrane electrode as described in any one of claims 13 to 15.